Directors' Liability in Negligence – Challenging the "Elements of the Tort" Approach - Stace, Victoria (Victoria University of Wellington Law Review, 2016)
This article suggests that the "elements of the tort" approach to directors' liability in negligence to third parties should be discontinued on the basis that assumption of responsibility as a threshold test is not an element of the tort of negligence or negligent misstatement and a more constructive approach would be to address the policy issues associated with imposing liability on directors as part of the two-stage duty of care inquiry.